The influence of critical thinking on academic resilience among university students in China. - Sihang , Zhang; Siew Ping, Wong (Journal of Islamic, Social, Economics and Development, 2025)
Among Chinese college students, this study looks at the correlation between two important factors: critical thinking abilities and academic resilience. It is crucial to comprehend the role of critical thinking in helping Chinese college students manage the rigorous academic environment. Finding out if there is a strong relationship between academic resilience and critical thinking skills is the primary goal of this study. Five hundred Chinese undergraduates from a variety of universities in different regions participated in a cross-sectional study that used a quantitative methodology. Students' critical thinking abilities were measured by administering the Critical Thinking Disposition Scale (CTDS) and their academic resilience by administering the Academic Resilience Scale (ARS). By using stratified random sampling, we were able to collect data from a large and diverse pool of respondents, which allowed us to examine all of these factors in the context of China's higher education system. Subjects assessed their critical thinking propensity and academic resilience with self-administered questionnaires. Critical thinking was moderate and academic resilience was relatively, according to descriptive statistics. Students who demonstrated higher levels of critical thinking were more likely to show resilience when confronted with academic difficulties, according to correlation analysis, which revealed a strong positive relationship between the two concepts. Independent of demographic characteristics, multiple regression analysis further showed that academic resilience was predicted by critical thinking skills. These results highlight the significance of teaching kids to think critically in order to help them succeed academically and overcome challenges.